Women's perspective on online shopping versus traditional shopping : a case study in Kota Kinabalu area / Mariayati Awang - Awang, Mariayati (2012)
Shopping can defines as activity of selection and/or purchase goods or service. For some contents, it is considered leisure as well as an economic one. In association to man (manusia), shopping has their own significant relationship as needs and wants are fulfilled when it comes to purchasing products/ services (Dhalokia, 1999) especially women (South & Spitze, 1994). According to previous researchers, majority of women in the world prefer to do shopping as compared to others activities. There are two (2) types of shopping; Traditional (sometimes Conventional) and Online Shopping. As revolution in technology especially internet is advancing, shopping habits among women have shifted to online shopping; It is more convenient and time savvy. However, despite of the differences among Traditional and Online shopping, both of it has its own pros and cons. In view of that, this study will concerns on women frequency of shopping (in a month) and their choices of shopping either by traditional or online.